ANALISIS PEMAHAMAN TEOLOGIS DOKTRIN KAABAH DI KALANGAN ANGGOTA GEREJA MASEHI ADVENT HARI KETUJUH SE-KOTAMADYA PEMATANGSIANTAR - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2016)
The doctrine of Sanctuary really need to be understood fully by every member of the Seventh-day Adventist Church throughout Pematangsiantar municipality. The understanding of that subject was very important to all of Church members so that they held a needed to benefit of the preparation from the merit of priesthood of Christ for all who yearned to obtain eternal life in God’s Kingdom. Each member of the church needed to have a theological understanding of the doctrine of the Sanctuary. It mean to understand the death of Jesus on the cross as a Lamb of God who died and slain replaced the death of his people. It included an understanding of his mediation services. Soon after his ascension to heaven, Jesus inaugurated the High Priest of the New Covenant and the task mediation holy priesthood in the chamber as described in the daily service of the priest in earthly sanctuary. The last phase of the Priesthood ministration of Christ is to conduct of the cleansing of sins of His people from the book of the records in Heaven as described in the work of the high priest in the annual service in the Earthly sanctuary. Every church member should have such understanding in order to conduct the necessary preparatory work relating to investigative judgment that only those who have